Preservatives in Food Products ?óÔé¼ÔÇ£ Review - Anton Smith, A (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The objective of this review is to examine the available safety/toxicity literature on preservatives like olive polyphenols, microbial fermented tea, essential oil, parabens, and the micro organisms. Antimicrobial activities of microbial fermented tea are much less known than its health beneficial properties. These antimicrobial activities are generated by fermentation process with tea leaves as substrates. The essential oil of Thymus vulgaris L. showed highest antifungal efficacy, significant anti-aflatoxigenic efficacy, fungi toxicant and synthetic fungicidal effect. Parabens are readily absorbed through the gastrointestinal tract and are rapidly excreted in the urine. The Enterococcus genus, a member of the lactic acid bacteria (LAB) is found in the intestines of humans and other animals. Although sometimes associated with pathogenicity, these bacteria are used as probiotic cultures and nowadays extensively used for the production of bacteriocins the enterocins. This study gives a proof of using preservatives and its efficacy in food and food products.